Factors Related Work Load Stress Among Migrant Semi-Skilled Workers in Messaieed Qatar - Mutaqin, Zaenal (South East Asia Nursing Research, 2019)
Stress is a condition arising from the gap between the demands generated by the transaction between individual and environment with resources of the biological, psychological, or social system. This study aims to determine factors that led to the stress of Indonesian semi-skill migrant workers in Messaieed Qatar. Method using descriptive analytical study with cross-sectional design. The study sample was 70 respondents of semi skill Indonesia migrant workers in Messaieed Qatar. The results showed a relationship between physical condition with the level of stress (p value=0.000 with r=0.407), the better of physical condition the milder levels of stress. There is a relationship between psychological burden with the level of stress (p value=0.01 with r=0.305), the lighter of psychological burden the milder level of stress. There is no relationship between extreme weather with the level of stress (p value=0.252 with r=0.139). There is a relationship between workload with the level of stress (p value=0.001 with r=0.379), the lighter workload the milder level of stress. There was a relationship between neighborhood conditions with stress level (p value=0.000 with r=0.541), the better condition of the neighborhood the milder level of stress. Recommendations of this study are Messaieed Medical Center to provide counseling and education about stress, how to reduce the stress on their own and social support. Companies where the respondents worked need to make some modifications of the environment such as conducted sport activities, a regular of spiritual tutorial activities, and other positive activities.